INFLUENCE OF TIME OF NITROGEN SECOND DOSE FERTILIZATION MAIZE (Zea mays L.) VARIETIES IN NORTHERN GUINEA SAVANNAH OF NIGERIA - Ladan, K. M.; Hassan, A. H. (FUDMA JOURNAL OF SCIENCES, 2021)
The field trial was carried out to evaluate the effect of timing nitrogen second dose fertilization on the grain yield and yield components of some improved maize varieties. The field experiments was conducted at the Institute for Agricultural Research IAR-ABU Research Farm Samaru – Zaria and Military Cantonment Farm Jaji – Nigeria. Treatments consist of three maize varieties (SAMMAZ 14, SAMMAZ 15 and SAMMAZ 16) and six timings of nitrogen second dose of fertilizer application. Data were recorded on grain yield, number of cobs /plant, number of grain /row, cob(ear) diameter, cob(ear) weight and 100 grain weight. Treatments were laid out in a randomized complete block design (RCBD) with three replications. SAMMAZ 16 produced significantly higher grain yield and recorded superior yield characters over SAMMAZ 14 and 15. The results further showed that time of nitrogen second dose application 6 WAS outperformed other timings evaluated at both location. The study identified. SAMMAZ 16 and time 6 WAS appeared to be the option for increased maize grain yield in the study area